Developing Student Entrepreneurship Towards Global Markets Through International Collaboration: Developing Student Entrepreneurship Towards Global Markets Through International Collaboration - Indra, Indra Hastuti (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The aim of this community service is to establish a collaboration between Universitas Duta Bangsa Surakarta and TGBC Thailand to support the development of student entrepreneurship towards the global market. The main objective is to provide training and mentoring to students who have taken entrepreneurship courses so that the products they create can continue to grow and compete in international markets. Therefore, this activity is conducted to provide direct guidance to students, particularly in digital business management, export procedures, and global marketing strategies. This activity will last for four months using the case study method, designed to help students increase profits, customer numbers, and business turnover. The outcome of this activity is the improvement of the sustainability of students’ creative businesses, enabling them to penetrate international markets. This collaboration can encourage the emergence of new, sustainable entrepreneurs capable of competing in the global market.